2016
DOI: 10.1016/j.renene.2015.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies towards optimization of the production of 5-(chloromethyl)furfural (CMF) from glucose in a two-phase reactor

Abstract: a b s t r a c t 5-(Chloromethyl)furfural (CMF) is rapidly being established as a renewable platform chemical of great promise. The effects of mass transfer, reaction temperature, Hansen solvent parameters, solvent fraction, and initial glucose concentrations on yields of CMF, 5-(hydroxymethyl)furfural (HMF), 2-(hydroxyacetyl) furan (HAF), levulinic acid (LA), and humic matter were investigated in a two-phase system of 6 M HCl and an organic solvent. The ability of the solvent to extract HMF from the aqueous ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…Mechanistically, the process can be considered to involve the hydrolysis of cellulose into glucose subunits, acid‐catalyzed isomerization to fructose, dehydration to HMF, and nucleophilic substitution of the OH function of 1 for chloride. Parameterization studies have shown that the success of the reaction is critically dependent on the ability of the solvent to extract HMF into the organic phase, where the decomposition pathways that have long plagued the synthesis of HMF are shut down . However, the partition coefficient of HMF in water is greater than in any hydrophobic solvent, so the key here is the conversion of HMF into CMF, which is both insoluble in water and comparatively acid stable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, the process can be considered to involve the hydrolysis of cellulose into glucose subunits, acid‐catalyzed isomerization to fructose, dehydration to HMF, and nucleophilic substitution of the OH function of 1 for chloride. Parameterization studies have shown that the success of the reaction is critically dependent on the ability of the solvent to extract HMF into the organic phase, where the decomposition pathways that have long plagued the synthesis of HMF are shut down . However, the partition coefficient of HMF in water is greater than in any hydrophobic solvent, so the key here is the conversion of HMF into CMF, which is both insoluble in water and comparatively acid stable.…”
Section: Methodsmentioning
confidence: 99%
“…Parameterization studies have shown that the successo ft he reaction is critically dependent on the ability of the solventt oe xtract HMF into the organicp hase, where the decomposition pathwayst hat have long plagued the synthesis of HMF are shut down. [10] However,t he partition coefficient of HMF in water is greater than in any hydrophobic solvent, so the key here is the conversion of HMF into CMF, which is both insoluble in water and comparatively acid stable. It is quickly sequestered into the organic phase, where it remains.…”
mentioning
confidence: 99%
“…Hence, the main byproducts were the Unidentified, such as soluble polymers and insoluble humins. Although the structures and formation mechanisms of the Unidentified were not explicit, numerous works [49,50] argued that the Unidentified compounds were ascribed to the polymerization of HMF and intermediate dehydration products of fructose, in which HMF primarily played as crossing-linking agents. According to the results and conclusions, the possible reaction mechanism was proposed and showed in the Sch.…”
Section: Effect Of the Reaction Duration On The Conversion Of Glucosementioning
confidence: 99%
“…5‐hydroxymethylfurfural (5‐HMF) is an important platform chemical for producing fuels, polymers and chemicals, which can be prepared in several media. However, on account of the activity and instability of this molecule, large‐scale production of 5‐HMF is strongly limited by the separation and storage problems . Thus, other stable platform chemicals were developed as substitutes for 5‐HMF, such as levulinic acid (LA) and halogenated methyl furfurals …”
Section: Introductionmentioning
confidence: 99%